Eksplorasi Faktor-Faktor yang Mempengaruhi Keputusan Orang Tua Memilih Sekolah di SMK Negeri 4 Surakarta - Wardiyanti, Koes, Drs. Wiyadi, M.M., Ph.D, Ihwan Susila, Ph.D (2016)
The objectives of the research is to explore the facts which influence the parents' decisions for choosing school, especially in SMK N 4 Surakarta. The research method uses descriptive qualitative. The subject of the research (informan) is the parents and students in SMK N 4 Surakarta. The technique of collecting data uses deeper interview and it's supported by presentation of the data and draw conclusion. The finding of the research shows the factors which influence the parent's decisions for choosing SMK N 4 Surakarta based on the students' interest, after graduated from vocational secondary school, the image of the school which has many achievement, entrepreneur, the quality of teaching learning and school fee actually do not become the serious matter, but the parents also consider the cheap school fee for their children.